2016
DOI: 10.1371/journal.pone.0160434
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Mycobacterium tuberculosis Genotypic Lineage Distribution in Chile and Neighboring Countries

Abstract: Tuberculosis (TB), caused by the pathogen Mycobacterium tuberculosis (MTB), remains a disease of high importance to global public health. Studies into the population structure of MTB have become vital to monitoring possible outbreaks and also to develop strategies regarding disease control. Although Chile has a low incidence of MTB, the current rates of migration have the potential to change this scenario. We collected and analyzed a total of 458 M. tuberculosis isolates (1 isolate per patient) originating fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 36 publications
2
11
1
Order By: Relevance
“…Our results indicate that the isolated Mtb strain is the SIT42 type, which is among the most widespread spoligotype in humans worldwide ( 31 34 ), thus supporting the hypothesis of a human-to-dog transmission. This genotype is also reported to be strongly associated to multidrug resistance (MDR), mostly among human immunodeficiency virus (HIV) coinfected patients ( 35 , 36 ).…”
Section: Discussionsupporting
confidence: 81%
“…Our results indicate that the isolated Mtb strain is the SIT42 type, which is among the most widespread spoligotype in humans worldwide ( 31 34 ), thus supporting the hypothesis of a human-to-dog transmission. This genotype is also reported to be strongly associated to multidrug resistance (MDR), mostly among human immunodeficiency virus (HIV) coinfected patients ( 35 , 36 ).…”
Section: Discussionsupporting
confidence: 81%
“…However, it might have remained undetected due to limitations in the study's sample representativeness. Subsequent nation-wide studies of M. tuberculosis lineages demonstrated the Beijing lineage in Colombia (10), where the first case of multidrug-resistant tuberculosis by a rare Beijing strain was reported, and more recently, in Chile (9,11), where Beijing strains were found in isolates from Santiago.…”
Section: Discussionmentioning
confidence: 99%
“…In the remaining three countries (Chile, Colombia and Ecuador) no Beijing isolates were identified. Subsequent nationwide studies, however, found Beijing lineage isolates in Colombia and Chile (9)(10)(11). Ecuador is the only country among those considered in the study where this lineage had not been reported yet.…”
mentioning
confidence: 81%
“…The sublineages with the lowest prevalence are Beijing (0.99%), S (0.3%), Cameroon (0.16%), and AFRI (0.16%), belonging to lineages 2 and 4 (Table 1). The Beijing sublineage is of interest because of its high pathogenicity and virulence present in the urban population of Chile due to migration from Peru and Venezuela (Balcells et al, 2015;Lagos et al, 2016;Meza et al, 2014).…”
Section: Chilementioning
confidence: 99%
“…Soto Cabezas et al, 2020 reported that almost half of the XDR-TB cases analyzed (48%) had no previous anti-TB treatment, which highlights the need to evaluate TB control programs. For bordering countries, both Ecuador and Chile have reported an increase in Beijing sublineage strains, making Ecuador and Colombia additional areas identified as critical or hotspots for the prevalence of lineage 2 (Garzon-Chavez et al, 2020;Lagos et al, 2016).…”
Section: Brazil and Peru Are Hotspots For Tuberculosis In South Americamentioning
confidence: 99%